Korelasi Sidik Jari Teh Putih (Camellia sinensis) dan Aktivitas Antioksidannya Menggunakan Spektrofotometri Inframerah Transformasi Fourier (FTIR) dan Analisis Data Multivariat - Yusuf, Muhammad Shalahuddin; Hunaefi, Dase; Yuliana, Nancy Dewi (Jurnal Mutu Pangan : Indonesian Journal of Food Quality, 2025)
White tea, made from young tea leaves dried without enzymatic fermentation, retains higher antioxidant content and has a unique sensory profile based on its growing region and processing method. Fourier transform infrared resonance (FTIR) spectrophotometry measures the absorption of infrared radiation by molecular bonds, generating a unique fingerprint. FTIR can monitor changes in the chemical composition during tea processing. Each producer may have different processing techniques that affect tea quality. A study analyzed white tea samples from five producers in Java, Indonesia, using FTIR fingerprinting and antioxidant activity. Sample D from Central Java had the highest DPPH antioxidant activity, followed by samples E (from West Java), H (from East Java), and P and G (from West Java). FTIR fingerprint analysis identified common absorption peaks at wave numbers 1242 (ester), 1600–1400 (ring double bond), 3518 cm⁻¹ (phenol), 2360 (amine), and 1400–1200 cm⁻¹ (carbonyl). Orthogonal partial least squares–discriminant analysis (OPLS-DA) grouped the samples into two classes regardless of the region: D, E, and H in class 1, and P and G in class 2. Wave numbers attributed to amine, aromatic, and aldehyde groups were among the discriminating markers for class 1 and class 2. The results of OPLS analysis revealed a strong positive correlation between wave numbers 1258, 1342, 1466, 2392, and 2685 cm⁻¹. These wave numbers were found at higher intensities in sample D, which had the highest antioxidant activity. Thus, they can be used as important markers for white tea with good antioxidant activity.